2016
DOI: 10.1007/s00247-016-3672-1
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, tolerability and safety of pediatric hyperpolarized 129Xe magnetic resonance imaging in healthy volunteers and children with cystic fibrosis

Abstract: Background Hyperpolarized 129Xe is a promising contrast agent for MRI of pediatric lung function but its safety and tolerability in children have not been rigorously assessed. Objective To assess the feasibility, safety and tolerability of hyperpolarized 129Xe gas as an inhaled contrast agent for pediatric pulmonary MRI in healthy control subjects and in children with cystic fibrosis. Materials and methods Seventeen healthy control subjects (ages 6–15 years, 11 boys) and 11 children with cystic fibrosis (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 65 publications
4
75
1
1
Order By: Relevance
“…Isotopically enriched 129 Xe (83%) was polarized to approximately 15% (Model 9800; Polarean, Durham, North Carolina) and dispensed into a 1‐L Tedlar bag (Jensen Inert Products, Coral Springs, Florida). To avoid the anesthetic effects of Xe, the HP 129 Xe dose was set to 10% of total lung capacity, as measured using plethysmography, and balanced to 1 L with medical‐grade N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Isotopically enriched 129 Xe (83%) was polarized to approximately 15% (Model 9800; Polarean, Durham, North Carolina) and dispensed into a 1‐L Tedlar bag (Jensen Inert Products, Coral Springs, Florida). To avoid the anesthetic effects of Xe, the HP 129 Xe dose was set to 10% of total lung capacity, as measured using plethysmography, and balanced to 1 L with medical‐grade N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Hyperpolarized 129 Xe ventilation imaging quantifies regional ventilation and is sensitive to airway obstruction in a wide variety of diseases . The technique is safe and well‐tolerated for many populations, including pediatrics . Ventilation imaging relies on obtaining reliable, spin density–weighted images to quantify xenon regionally in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have performed HP 3 He MRI in CF patients (mostly adults) in order to investigate regional defects in ventilation (1316), HP gas repeatability (17,18), longitudinal ventilation changes (19), and treatment efficacy (2023). Use of 129 Xe in pediatrics is more restricted than 3 He due to its slightly higher Ostwald solubility (ratio of gas volume absorbed by a liquid to the liquid volume) and thus greater anesthetic effect at high doses, but recent studies have shown that single-breath- holds of sub-anesthetic doses of Xe present no safety concerns in adults (24) or children (25). Because of the increasing cost and scarcity of 3 He, HP gas research has recently shifted focus toward 129 Xe (26, 27), and indeed, there is some evidence that 129 Xe may be more sensitive than 3 He to early functional deficits (26) but CF research in pediatrics with HP 129 Xe MRI has not been reported.…”
Section: Introductionmentioning
confidence: 99%